An Analysis Of The Types Of Reading Question In The English Textbook "Bright" For The Seven Grade Of Junior High School Published By Erlangga - Muliasari., Dewi, Drs. Djoko Srijono, M.Hum, Mauly Halwat Hikmat, Ph. D (2014)
This research paper is aimed at finding the types of reading question in the textbook "Bright"for the seven grade student of Juior High School. The writer applies descriptive study as the type of this research. The data are collected by using document analysis technique. The data are the materials in the English textbook "Bright". The writer uses descriptive analysis as the technique for analyzing data, the steps are: (1) collecting the data in the "Bright" textbook, (2) tabulating the data into the table to find the types of reading text questions on the Bright textbook, (3) analyzing the data. The result of this study shows that there are five types of question in the English textbook "Bright". There are question of literal comprehension, question involving reorganization or reinterpretatin, question of inference, question of evaluation, and question of personal response. The dominan question is question of literal comprehension.